Ernst Fuchs (1851-1930) and the Worldwide Renown of the Vienna School of Ophthalmology around 1900 A documentary biography - Schmidt-Wyklicky, Gabriela (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
By presenting documents and original photographs of the ophthalmologist Ernst Fuchs his life and scientific work are presented in a way never done before. German Version: http://e-book.fwf.ac.at/o:1551 English Version: http://e-book.fwf.ac.at/o:1773